Association of physical activity with sleep health: A systematic review - Andrea Wendt; Thaynã Ramos Flores; Inácio Crochemore Mohnsam Silva; Fernando César Wehrmeister (Revista Brasileira de Atividade Física e Saúde)
The aim of this study was to systematically examine the literature on physical activity and sleep in non-clinical and population-based settings. The inclusion criteria were original studies testing the association between physical activity (as exposure) and sleep (as outcome) in representative samples of the general population, workers, or undergraduate students. Sleep health included sleep duration, sleep quality and insomnia. Studies evaluating samples including only individuals with some disease or a health condition were excluded. A search was performed in the PubMed, Scopus, Lilacs, CINAHL, and SPORTdiscus databases in March 2018. Data extraction was performed using the following items: year, author, country, population, age group, sample size, study design, sleep measurement/definition, physical activity measurement/definition, adjustment and main results. A total of 57 studies were selected, which markedly used heterogeneous instruments to measure physical activity and sleep. The majority were conducted in high-income countries and with cross-sectional design. Physical activity was associated with lower odds of insomnia (observed in 10 of 17 studies), poor sleep quality (observed in 12 of 19 studies) and long sleep duration (observed in 7 of 11 studies). The results about short sleep or continuous sleep duration remain unclear. Physical activity seems to be associated with sleep quality and insomnia, especially among adult and elderly populations in which these outcomes are more usually measured. The short- and long-term effects of physical activity intensities and dose-response on sleep should be better evaluated.